OPTIMIZATION OF COMPLEX THERAPY OF PATIENTS WITH LOCALIZED SCLERODERMA - Обадех Махмуд Ал-Омарi (World of Medicine and Biology, 2022)
In this article, we consider the most important aspects and features of the treatment of patients with a diagnosis of localized scleroderma. In the course of the disease, there is a violation of the metabolism of connective tissues with the development of hyperproduction of collagen by fibroblasts. One of the reasons for this condition is a violation of the ratio of oxidants and antioxidants. The aim of the work was to increase the efficiency of diagnosis and treatment of localized scleroderma based on the study of endothelial, endotoxic and pro-oxidant metabolic disorders in patients, their relationship with the severity of the disease and the effectiveness of pharmacotherapy. The paper investigates the role of endothelial disorders, oxidative stress and endotoxicosis in the pathogenesis of localized scleroderma. The connection of certain metabolic disorders with the severity of the disease and clinical forms of dermatosis was revealed. It should be noted that the use of complex therapy, which included the appointment of L-arginine, an antioxidant drug – thioctic acid, colloidal silicon dioxide, ultraphonophoresis with hyaluronidase, corrected metabolic disorders in the body of patients with localized scleroderma, reduced the levels of endothelial markers, manifestations of endotoxicosis, restored the balance in the system of pro- and antioxidants, reduced the intensity of free radical oxidation processes. The proposed complex therapy of dermatosis in comparison with other proposed methods of treatment of scleroderma shows high clinical effectiveness, shortens the treatment period and prolongs the clinical remission of dermatosis.